Heat transfer and turbulent flow friction in a round tube with staggered-winglet perforated-tapes - Skullong, Sompol; Promvonge, Pongjet; Thianpong, Chinaruk; Pimsarn, Monsak (My University, 2016)
The article deals with thermal and flow resistance characteristics in a tubular heat exchanger fitted with staggered-winglet perforated tapes (WPT). The experiment was conducted in the test tube having a constant wall heat-flux for turbulent airflow, Reynolds number (Re) from 4180 to 26,000. The aim of using the WPT is to generate longitudinal vortex flows to disrupt thermal boundary layer on the tube wall and to provide stronger fluid mixing. The WPT having an winglet inclination angle of 30° was inserted into the test tube at five different winglet blockage ratios (B R = 0.1, 0.15, 0.2, 0.25 and 0.3) and three winglet pitch ratios (P R = 0.5, 1.0 and 1.5). To find an optimum thermal performance condition, the effect of B R and P R on the heat transfer and pressure loss due to flow friction in the tube is examined. The experimental results reveal that Nusselt number (Nu) and friction factor (f) for the WPT increase with the increment of B R but the reduction of P R . The highest thermal enhancement factor (TEF) of 1.71 is achieved by utilizing the WPT with B R = 0.15, P R = 1.0 at Re = 4180. Compared to staggered-winglet typical non-perforated tape (WTT), the WPT yields the TEF of about 1.2 times higher than the WTT. Correlations of Nu, f and TEF for the WPT and the WTT are also proposed.
Keywords: Heat exchanger; Perforated tape; Staggered winglet; Thermal performance; Vortex generator